MISTERI RADAR DI BUKIT KAMPUNG BARUKI DISTRIK NUMFOR BARAT (Mystery of Radar in Baruki Village, West Numfor District) - Suryo, Almuchalif (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2019)
Numfor Island is located in Cenderawasih Bay. Numfor Island is one of the strategic islands that were established by Japan and the Allies during the Pacific War. To protect Biak Island from the threat of enemy aircraft, the Dutch set up radar in West Numfor. From existing references that the Dutch put the MK IV type 15 radar made in England. This radar has a range of up to 200 NM. The need for socialization about the existence of this tower as a warissan cultural heritage protected by law, so that this tower does not disappear slowly without a trace. ABSTRAKPulau Numfor terletak di Teluk Cenderawasih. Pulau Numfor merupakan salah satu pulau yang strategis yang diperbutkan oleh Jepang dan Sekutu pada masa Perang Pasifik. Untuk melindungi Pulau Biak dari ancaman pesawat udara musuh, maka Belanda mendirikan radar di Numfor Barat. Dari referensi yang ada bahwa Belanda menempatkan radar jenis MK IV tipe 15 buatan Inggris. Radar ini memiliki daya jangkau sampai 200 NM. Perlunya sosialisasi tentang keberadaan tower ini sebagai warissan cagar budaya yang dilindungi oleh undang-undang, agar tower ini tidak hilang secara perlahan-lahan tanpa bekas.